Meningkatkan Nasionalisme dan Spiritualitas Anak Jalanan dengan Program Pembelajaran Anak Negeri - Abdillah dkk, Diaz Syafrie (LPPPM STAI Darul Hikmah Bangkalan, 2018)
Street children are children who spend most of their time earning a living, wandering the streets or other public places. This program is an innovation in the field of community service called the